N2-tert-Butoxycarbonyl-N5-[N-(9-fluorenylmethyloxycarbonyl)-2-aminoethyl]-(S)-2,5-diaminopentanoic Acid - Jyotirmoy Maity; Roger Stromberg (Molbank, 2014)
N2-tert-Butoxycarbonyl-N5-[N-(9-fluorenylmethyloxycarbonyl)-2-aminoethyl]-(S)-2,5-diaminopentanoic acid (5) has been synthesized by the reaction of N2-tert-butoxycarbonyl-L-2,5-diaminopentanoic acid (Boc-L-ornithine, 3) and N-Fmoc-2-aminoacetaldehyde (N-Fmoc-glycinal, 4) in the presence of sodium cyanoborohydride in methanol containing 1% acetic acid at room temperature.